The Second Zagreb Eccentricity Coindex of Composite Graphs - Azari, Mahdieh (Utilitas Mathematica, 2020)
The second Zagreb eccentricity coindex is defined as the total eccentricity product of all non-adjacent vertex pairs in a connected graph. In this paper, we present explicit formulae for the values of the second Zagreb eccentricity coindex for some families of composite graphs. Results are applied to some graphs of chemical and general interest. © 2020 Utilitas Mathematica Publishing Inc.. All rights reserved.